Thermoplastic elastomer composition, molded body, and airbag storage cover

JP7643122B2Active Publication Date: 2025-03-11MITSUBISHI CHEM CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021048265
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-23
Publication Date
2025-03-11
Estimated Expiration
2041-03-23

AI Technical Summary

Benefits of technology

【0019】 本発明の熱可塑性エラストマー組成物は、高温強度、低温耐衝撃性、および離型性に優れたものである。このため、本発明の熱可塑性エラストマー組成物によれば、高温強度、低温耐衝撃性、および離型性に優れたエアバッグ収納カバーが提供される。 本発明のエアバッグ収納カバーは、運転席用エアバッグ収納カバー、助手席用エアバッグ収納カバー、歩行者用エアバッグ収納カバー、ニー·エアバッグ収納カバー、サイド·エアバッグ収納カバー、カーテン·エアバッグ収納カバー等のいずれにも好適に用いることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643122000001
    Figure 0007643122000001
Patent Text Reader

Abstract

To provide a thermoplastic elastomer composition excellent in high-temperature strength, low-temperature impact resistance, and releasability, and to provide a molding and an air bag housing cover comprising the thermoplastic elastomer composition.SOLUTION: The thermoplastic elastomer composition contains at least the following components (A)-(C): (A) a propylene-based polymer; (B) an olefinic block copolymer which contains a polymer block comprising ethylene and an ethylene / α-olefin copolymer block; and (C) a high-density polyethylene. The ratio of the mass of the component (B) to the mass of the component (A) is 0.6 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic elastomer composition having excellent high-temperature strength, low-temperature impact resistance and mold releasability, and to a molded article and an airbag storage cover using this thermoplastic elastomer composition. [Background technology]

[0002] An automobile airbag system protects the driver and passengers in the event of a collision, and is made up of a device that detects the impact of the collision and an airbag device. This airbag device is installed in the steering wheel, the instrument panel in front of the passenger seat, the driver's and passenger's seats, the front and side pillars, etc.

[0003] When the airbag is inflated, there is a concern that the airbag storage cover in an airbag device may break and cause fragments to fly off, or that the cover attachment portion may break and cause the cover to fly off. For this reason, various proposals have been made regarding the structure and materials of the cover to prevent the cover from breaking abnormally and flying off.

[0004] Conventionally, as a material for an airbag storage cover, for example, Patent Document 1 proposes a thermoplastic elastomer obtained by dynamically heat treating a propylene-based resin, an ethylene-α-olefin copolymer, a compatibilizer, and high-density polyethylene in the presence of an organic peroxide. Patent Documents 2 and 3 propose a material made of an olefin-based block copolymer including a polymer block made of a propylene-based resin, high-density polyethylene, and ethylene, and an ethylene-α-olefin copolymer block. Patent Document 4 proposes an airbag storage cover made of a thermoplastic elastomer made of a propylene-based resin, an ethylene-α-olefin copolymer, and low-density polyethylene. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2013-203937 A [Patent Document 2] Special Publication No. 2019-517601 [Patent Document 3] Special Publication No. 2019-517609 [Patent Document 4] JP 2018-35297 A Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, there has been concern about damage to airbag storage covers at low and high temperatures due to improved airbag deployment power, and therefore there is a demand for the development of a thermoplastic elastomer composition as a material with improved high-temperature strength and low-temperature impact resistance from the viewpoints of enhanced safety, design freedom, etc. In addition, it is necessary to prevent problems with release from the mold when molding airbag storage covers, and therefore a material with excellent release properties is desired.

[0007] However, after detailed investigations by the present inventors, it was found that the materials for conventional airbag storage covers such as those described in Patent Documents 1 to 4 above were insufficient in terms of high-temperature strength, low-temperature impact resistance, and mold releasability.

[0008] The present invention has been made in consideration of the above-mentioned problems in the prior art. That is, an object of the present invention is to provide a thermoplastic elastomer composition having excellent high-temperature strength, low-temperature impact resistance and mold releasability, and a molded article and an airbag storage cover made of said thermoplastic elastomer composition. [Means for solving the problem]

[0009] Means for Solving the Problems The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that a thermoplastic elastomer composition containing a propylene-based polymer and an olefin-based block copolymer containing a polymer block composed of ethylene and an ethylene-α-olefin copolymer block in a specific blend ratio, and containing high-density polyethylene, has excellent high-temperature strength, low-temperature impact resistance and mold releasability, thereby completing the present invention. That is, the gist of the present invention lies in the following [1] to [9].

[0010] [1] A thermoplastic elastomer composition comprising at least the following components (A) to (C), in which the mass ratio of component (B) to component (A) is 0.6 or more: Component (A): Propylene-based polymer Component (B): An olefin block copolymer containing a polymer block made of ethylene and an ethylene-α-olefin copolymer block. Component (C): High density polyethylene

[0011] [2] The thermoplastic elastomer composition according to [1], wherein the contents of components (A) to (C) in the thermoplastic elastomer composition are in the order of: content of component (A) > content of component (B) > content of component (C).

[0012] [3] The thermoplastic elastomer composition according to [1] or [2], wherein the component (B) has a crystalline melting peak at 110 to 125°C and a crystalline melting heat of 20 to 60 J / g.

[0013] [4] The thermoplastic elastomer composition according to any one of [1] to [3], wherein the α-olefin in the ethylene-α-olefin copolymer block of component (B) has 4 to 8 carbon atoms.

[0014] [5] The thermoplastic elastomer composition according to any one of [1] to [4], wherein the component (B) is an olefin-based block copolymer comprising a polymer block of ethylene and an ethylene-1-octene copolymer block.

[0015] [6] The thermoplastic elastomer composition according to any one of [1] to [5], wherein the component (A) is a propylene-based block copolymer obtained by polymerizing a propylene homopolymer in a first step and then polymerizing a propylene-ethylene copolymer in a second step.

[0016] [7] The plastic elastomer composition according to any one of [1] to [6], wherein the component (A) has a melt flow rate (measured at 230°C and a load of 21.18 N) of 10 to 150 g / 10 min.

[0017] [8] A molded article obtained by injection molding the thermoplastic elastomer composition according to any one of [1] to [7].

[0018] [9] An airbag storage cover comprising the thermoplastic elastomer composition according to any one of [1] to [7]. Effect of the Invention

[0019] The thermoplastic elastomer composition of the present invention is excellent in high-temperature strength, low-temperature impact resistance, and mold releasability. Therefore, the thermoplastic elastomer composition of the present invention provides an airbag storage cover that is excellent in high-temperature strength, low-temperature impact resistance, and mold releasability. The airbag storage cover of the present invention can be suitably used as a driver's airbag storage cover, a passenger's airbag storage cover, a pedestrian airbag storage cover, a knee airbag storage cover, a side airbag storage cover, a curtain airbag storage cover, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The present invention will be described in detail below, but the present invention is not limited to the following description, and can be modified as desired without departing from the gist of the present invention. In the present invention, when a numerical value or physical property value is enclosed before and after "~", the value before and after the "~" is included.

[0021] [Thermoplastic elastomer composition] The thermoplastic elastomer composition of the present invention is a thermoplastic elastomer composition containing the following components (A) to (C), in which the mass ratio of component (B) to component (A) is 0.6 or more. Component (A): Propylene-based polymer Component (B): An olefin block copolymer containing a polymer block made of ethylene and an ethylene-α-olefin copolymer block. Component (C): High density polyethylene

[0022] When the thermoplastic elastomer composition of the present invention is used as a raw material for an airbag storage cover, it has the effects of being superior in high-temperature strength, low-temperature impact resistance, and mold releasability compared to the case where a conventional thermoplastic elastomer composition is used. The reason why this effect occurs is not clear, but is speculated to be as follows. The polymer block made of ethylene contained in component (B) and the high-density polyethylene of component (C) show good compatibility, which improves the dispersibility of components (B) and (C) in the thermoplastic elastomer composition. This makes the interfaces between the components unclear when considered microscopically, which is thought to improve mechanical properties such as high-temperature strength and low-temperature impact resistance. In addition, the domains formed by the high-density polyethylene of component (C) moderately roughen the molded surface during molding, which is thought to improve demolding properties. Furthermore, setting the ratio of mass of component (B) / mass of component (A) to 0.6 or more means that a specified amount or more of component (B) having a low glass transition temperature is blended. By blending in this manner, it is possible to further improve low-temperature impact resistance without impairing high-temperature strength or demolding properties.

[0023] In the present invention, the term "airbag storage cover" refers to the container that stores an airbag in general, and is, for example, the opening through which the airbag deploys in a container that stores an airbag, or the entire container that is integrated with this opening.

[0024] <Component (A)> Component (A) used in the thermoplastic elastomer composition of the present invention is a propylene-based polymer, and is mainly composed of propylene units. The propylene unit content of the propylene-based polymer of component (A) is preferably 85 to 100 mass%, more preferably 90 to 100 mass%. When the propylene unit content of component (A) is equal to or more than the lower limit, the heat resistance and rigidity tend to be good. The propylene unit content in component (A) can be determined by infrared spectroscopy.

[0025] Component (A) may be a propylene homopolymer or a propylene copolymer containing, in addition to propylene units, preferably 15% by mass or less, more preferably 10% by mass or less, of ethylene units, α-olefin units other than propylene, monomer units other than ethylene and α-olefins, etc. The propylene copolymer may be a propylene random copolymer or a propylene block copolymer.

[0026] Examples of the α-olefin unit other than propylene include α-olefins having 4 to 20 carbon atoms. Examples of α-olefins having 4 to 20 carbon atoms include 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 2-ethyl-1-hexene, and 2,2,4-trimethyl-1-pentene. α-olefins having 4 to 10 carbon atoms are preferred, and ethylene, 1-butene, 1-hexene, and 1-octene are more preferred. The propylene-α-olefin copolymer may contain only one kind of these α-olefin units, or may contain two or more kinds of them.

[0027] Specific examples of the propylene-based polymer of component (A) include propylene homopolymer, propylene-ethylene copolymer, propylene-1-butene copolymer, propylene-1-hexene copolymer, propylene-1-octene copolymer, propylene-ethylene-1-butene copolymer, propylene-ethylene-1-hexene copolymer, propylene-ethylene-1-octene copolymer, propylene-based block copolymer obtained by polymerizing propylene homopolymer in the first step and subsequently polymerizing propylene-ethylene copolymer in the second step, etc. Preferred are propylene homopolymer, copolymer of propylene and at least one monomer selected from ethylene and α-olefins having 4 to 10 carbon atoms, and propylene-based block copolymer obtained by polymerizing propylene homopolymer in the first step and subsequently polymerizing propylene-ethylene copolymer in the second step. Among these, from the viewpoints of low-temperature impact resistance and high-temperature strength, it is particularly preferable that component (A) be a propylene-based block copolymer obtained by polymerizing a propylene homopolymer in the first step and then polymerizing a propylene-ethylene copolymer in the second step.

[0028] The melt flow rate (MFR) of component (A) is not limited, but is usually 0.1 g / min or more, and from the viewpoint of the appearance of the molded product, it is preferably 10 g / 10 min or more, more preferably 20 g / 10 min or more, and even more preferably 25 g / 10 min or more. The melt flow rate of component (A) is usually 200 g / 10 min or less, and from the viewpoint of tensile strength, it is preferably 150 g / 10 min or less, more preferably 100 g / 10 min or less. The melt flow rate of component (A) is measured according to JIS K7210 (1999) under the conditions of a measurement temperature of 230° C. and a measurement load of 21.18 N.

[0029] The propylene polymer of component (A) can be produced by a known polymerization method using a known olefin polymerization catalyst. For example, a multi-stage polymerization method using a Ziegler-Natta catalyst can be used. The multi-stage polymerization method can be a slurry polymerization method, a solution polymerization method, a bulk polymerization method, a gas phase polymerization method, or the like, or two or more of these methods can be combined.

[0030] In addition, the component (A) used in the thermoplastic elastomer composition of the present invention may be a commercially available product. The propylene-based polymer of component (A) can be procured from the manufacturers listed below and can be appropriately selected. Available commercial products include, for example, Prim Polypro (registered trademark) from Prime Polymer, Sumitomo Noblen (registered trademark) from Sumitomo Chemical, polypropylene block copolymer from SunAllomer, Novatec (registered trademark) PP from Japan Polypropylene, Moplen (registered trademark) from LyondellBasell, ExxonMobil PP from ExxonMobil, Formolene (registered trademark) from Formosa Plastics, Borealis PP from Borealis, SEETEC PP from LG Chemical, ASI POLYPROPYLENE from A. Schulman, INEOS PP from INEOS Olefins & Polymers, Braskem PP from Braskem, Samsung Total from SAMSUNG TOTAL PETROCHEMICALS, Sabic (registered trademark) PP from Sabic, TOTAL PETROCHEMICALS Polypropylene from TOTAL PETROCHEMICALS, and YUPLENE (registered trademark) from SK.

[0031] The thermoplastic elastomer composition of the present invention may contain only one type of propylene-based polymer as component (A), or may contain two or more types having different monomer compositions, physical properties, etc.

[0032] <Ingredient (B)> The component (B) used in the thermoplastic elastomer composition of the present invention is an olefin block copolymer containing a polymer block made of ethylene and an ethylene-α-olefin copolymer block.

[0033] It is preferable that component (B) has a crystalline melting peak at 110 to 125°C and the crystalline melting heat is 20 to 60 J / g. Here, in component (B), the crystalline melting heat of 20 to 60 J / g at the crystalline melting peak at 110 to 125°C is an index showing that component (B) has a polymer block made of crystalline ethylene. Furthermore, component (B) has amorphousness based on the ethylene-α-olefin copolymer block in addition to crystallinity based on the polymer block made of ethylene. By component (B) having such a structure, the thermoplastic elastomer composition of the present invention is given the effects of high-temperature strength and low-temperature impact resistance. The crystalline melting heat of component (B) is more preferably 30 J / g or more from the viewpoint of high-temperature strength. Furthermore, the crystalline melting heat of component (B) is more preferably 50 J / g or less from the viewpoint of low-temperature impact resistance.

[0034] The polymer block made of ethylene in component (B) is mainly made of ethylene, but may have other monomer units in addition to ethylene. Examples of other monomer units include 1-propylene, 1-butene, 2-methylpropylene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, etc. Preferred are α-olefins having 3 to 8 carbon atoms and having a carbon-carbon double bond at the terminal carbon atom, such as 1-propylene, 1-butene, 1-hexene, and 1-octene. The polymer block made of ethylene in component (B) may be one in which only one type of α-olefin is copolymerized with ethylene, or two or more types of α-olefins are copolymerized with ethylene.

[0035] Examples of the ethylene-α-olefin copolymer block of component (B) include those having 1-propylene, 1-butene, 2-methylpropylene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, etc. as an α-olefin as a structural unit in addition to ethylene units. Preferred are α-olefins having 4 to 8 carbon atoms and having a carbon-carbon double bond at the terminal carbon atom, such as 1-propylene, 1-butene, 1-hexene, and 1-octene. The ethylene-α-olefin copolymer block of component (B) may be one in which only one type of α-olefin is copolymerized with ethylene, or two or more types of α-olefins may be copolymerized with ethylene.

[0036] The ethylene-α-olefin copolymer block in component (B) may have other monomer units such as monomer units based on non-conjugated dienes (non-conjugated diene units) in addition to ethylene units and α-olefin units having 3 to 8 carbon atoms. Examples of the non-conjugated dienes include linear non-conjugated dienes such as 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, and 7-methyl-1,6-octadiene; and cyclic non-conjugated dienes such as cyclohexadiene, dicyclopentadiene, methyltetrahydroindene, 5-vinylnorbornene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, 5-isopropylidene-2-norbornene, and 6-chloromethyl-5-isopropenyl-2-norbornene. Preferred are 5-ethylidene-2-norbornene and dicyclopentadiene.

[0037] The content of ethylene units in component (B) is preferably 50% by mass or more and 80% by mass or less based on the total content of ethylene units and α-olefin units. The content of ethylene units in component (B) is preferably high in order to prevent fusion due to blocking of component (B), and low in terms of low-temperature impact resistance when the thermoplastic elastomer of the present invention is molded. The content of ethylene units in component (B) is more preferably 55% by mass or more, and even more preferably 60% by mass or more. The content of ethylene units is more preferably 75% by mass or less. The content of ethylene units and the content of α-olefin units having 4 to 8 carbon atoms in component (B) can each be determined by infrared spectroscopy.

[0038] When the ethylene-α-olefin copolymer block in component (B) contains other monomer units such as non-conjugated diene units, the content thereof is usually 10% by mass or less, and preferably 5% by mass or less, based on the total amount of component (B). The content of the non-conjugated diene units can also be determined by infrared spectroscopy.

[0039] Specific examples of the component (B) used in the thermoplastic elastomer composition of the present invention include block copolymers containing a polymer block made of ethylene and an ethylene-α-olefin copolymer block, such as an ethylene-1-butene copolymer, an ethylene-1-hexene copolymer, an ethylene-1-octene copolymer, an ethylene-propylene-1-butene copolymer, an ethylene-propylene-1-hexene copolymer, or an ethylene-propylene-1-octene copolymer. It can be shown. The polymer block made of ethylene and the ethylene-α-olefin copolymer block may each be used alone or in combination of two or more kinds. Among these, it is most preferable that component (B) is a block copolymer containing a polymer block made of ethylene and an ethylene-1-octene copolymer block, i.e., component (B) is an olefin-based block copolymer containing a polymer block made of ethylene and an ethylene-1-octene copolymer block.

[0040] Component (B) has a polymer block made of crystalline ethylene, and also has amorphousness due to the ethylene-α-olefin copolymer block. This amorphousness can be expressed by the glass transition temperature, and the glass transition temperature of component (B) measured by the DSC method is preferably -80°C or higher, more preferably -75°C or higher, and on the other hand, is preferably -50°C or lower, more preferably -60°C or lower.

[0041] The melt flow rate (MFR) of component (B) is not limited, but is usually 10 g / 10 min or less, and from the viewpoint of strength, it is preferably 8.0 g / 10 min or less, more preferably 5.0 g / 10 min or less, and even more preferably 3.0 g / 10 min or less. The melt flow rate of component (B) is usually 0.01 g / 10 min or more, and from the viewpoint of fluidity, it is preferably 0.05 g / 10 min or more, more preferably 0.10 g / 10 min or more. The melt flow rate of component (B) is measured according to ASTM D1238 under the conditions of a measurement temperature of 190 ° C. and a measurement load of 21.18 N.

[0042] From the viewpoint of low-temperature impact resistance, the density of component (B) is preferably 0.88 g / cm 3 On the other hand, the lower limit is not particularly limited, but is usually 0.85 g / cm 3 The density of component (B) is a value measured in accordance with ISO 1183-A at a measurement temperature of 23°C.

[0043] The component (B) can be synthesized according to the methods disclosed in JP-A-2007-529617, JP-A-2008-537563, and JP-A-2008-543978. For example, the component (B) can be produced by preparing a composition containing a mixture or reaction product obtained by combining a first olefin polymerization catalyst, a second olefin polymerization catalyst capable of preparing a polymer having different chemical or physical properties from the polymer prepared by the first olefin polymerization catalyst under the same polymerization conditions, and a chain shuttling agent, and contacting the composition with the ethylene and α-olefin under addition polymerization conditions.

[0044] The polymerization of component (B) is preferably carried out by a continuous solution polymerization method. In the continuous solution polymerization method, the catalyst components, the chain shuttling agent, the monomers, and optionally the solvent, the auxiliary, the scavenger and the polymerization aid are continuously fed into a reaction zone, and the polymer product is continuously taken out therefrom. The length of the block can be changed by controlling the ratio and type of the catalyst, the ratio and type of the chain shuttling agent, the polymerization temperature, etc.

[0045] Other conditions for the synthesis of the olefin block copolymer of component (B) are disclosed in JP-A-2007-529617, JP-A-2008-537563, and JP-A-2008-543978.

[0046] In addition, the component (B) used in the thermoplastic elastomer composition of the present invention may be a commercially available product. Examples of commercially available products of the component (B) include the Engage (registered trademark)-XLT series and INFUSE (registered trademark) series manufactured by Dow Chemical Company.

[0047] The thermoplastic elastomer composition of the present invention may contain only one type of olefin block copolymer as component (B), or may contain two or more types having different monomer compositions, physical properties, etc.

[0048] <Component (C)> The high density polyethylene used as component (C) has a density of 0.94 to 0.97 g / cm 3 , preferably 0.95 to 0.97 g / cm 3 In the present invention, the density of the high density polyethylene is a value measured in accordance with JIS K6760. The density of component (C) is 0.94 g / cm 3 If the density is 0.97 g / cm or more, the rigidity and tensile elongation at break of the obtained molded article tend to be good. 3 When it is equal to or less than this, the toughness and appearance of the obtained molded article tend to be good.

[0049] The melt flow rate (MFR) of component (C), measured according to ASTM D1238 at a temperature of 190°C and a load of 21.18N, is preferably 0.01 to 5 g / 10 min, more preferably 0.05 to 1 g / 10 min. By setting the MFR of component (C) to the lower limit or higher, good moldability and appearance tend to be obtained. By setting the MFR to the upper limit or lower, good low-temperature impact resistance tends to be maintained.

[0050] The high density polyethylene of component (C) may be a homopolymer of ethylene, or a copolymer of ethylene with one or more α-olefins having 3 to 20 carbon atoms, preferably 4 to 10 carbon atoms, such as propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, and 1-eicodecene.

[0051] When the high-density polyethylene is produced by a medium-low pressure process as an ethylene homopolymer or a copolymer of ethylene and a small amount of α-olefin, and is a copolymer of ethylene and α-olefin, the content of ethylene units in the high-density polyethylene is preferably 80% by mass or more, particularly 90% by mass or more, and the content of α-olefin units is preferably 0.1 to 10% by mass, from the viewpoint of the balance between rigidity and toughness. Here, the contents of ethylene units and α-olefin units in the high-density polyethylene can be determined by infrared spectroscopy.

[0052] High density polyethylene is usually obtained by homopolymerization of ethylene or copolymerization of ethylene and an α-olefin using a catalyst consisting of a transition metal compound and an organometallic compound.

[0053] Examples of the transition metal compound of the catalyst include one or more compounds of transition metals such as titanium, vanadium, chromium, etc., or compounds in which these are supported or reacted with silica, alumina, magnesium compounds, etc. In particular, solid catalyst components in which titanium compounds such as titanium chloride, haloalcoholates, and alcoholates are supported or reacted with magnesium compounds such as magnesium dialcoholates and magnesium chloride are preferably used.

[0054] The organometallic compounds include those of the general formula AlR n X 3-n (wherein R is a hydrocarbon group having 1 to 14 carbon atoms, X is a halogen atom, and n is an integer of 1 to 3.) Specific examples include triethylaluminum, tri-n-propylaluminum, triisobutylaluminum, dimethylaluminum monochloride, and ethylaluminum sesquichloride.

[0055] Commercially available high-density polyethylenes may also be used as component (C). Examples of commercially available products of component (C) include Novatec (registered trademark) HD ​​from Japan Polyethylene Corporation, Creolex (registered trademark) and Suntec-HD (registered trademark) from Asahi Kasei Chemicals Corporation, Hi-Zex (registered trademark) and Evolue H (registered trademark) from Prime Polymer Corporation, and QAMAR-HD (registered trademark) from Saudi Petrochemical Company.

[0056] Biopolyethylene containing plant-derived ethylene can also be used as high-density polyethylene. Biopolyethylene generally has a density of 0.942 g / cm 3 More than 0.980g / cm 3 The following can be used, the density of which is preferably 0.945 to 0.970 g / cm 3 , more preferably 0.948 to 0.965 g / cm 3 The density of the bio-polyethylene was measured in accordance with JIS K6922-2. The biopolyethylene that can be used has an MFR (measured in accordance with JIS K6922-2 at a temperature of 190° C. and a load of 21.18 N) of usually 1 to 100 g / 10 min, preferably 5 to 80 g / 10 min, and more preferably 10 to 50 g / 10 min. A commercially available bio-polyethylene product is plant-derived high-density polyethylene, a type of green polyethylene manufactured by Braskem (Brazil).

[0057] In the present invention, the high density polyethylene as component (C) may be used alone or in combination of two or more kinds having different physical properties, types of copolymerization components, ethylene unit contents, etc.

[0058] <Mixing ratio> The thermoplastic elastomer composition of the present invention preferably has the following content ratio of components (A) to (C) in the thermoplastic elastomer composition: content of component (A) > content of component (B) > content of component (C). By blending components (A) to (C) so that the content ratio satisfies the above relationship, it is possible to obtain a molded article having low-temperature impact resistance while controlling the flexural modulus within a suitable range.

[0059] The thermoplastic elastomer composition of the present invention preferably contains 25 to 60 mass% of component (A), 20 to 55 mass% of component (B), and 3 to 25 mass% of component (C) relative to a total of 100 mass% of components (A) to (C), and more preferably contains 30 to 50 mass% of component (A), 25 to 50 mass% of component (B), and 5 to 20 mass% of component (C).

[0060] When the content of component (A) is equal to or higher than the above lower limit, the heat resistance and moldability are good, and when it is equal to or lower than the above upper limit, the low-temperature impact resistance is good. When the content of component (B) is equal to or higher than the above lower limit, the low-temperature impact resistance is good, and when it is equal to or lower than the above upper limit, the rigidity and mechanical strength are high. When the content of component (C) is equal to or higher than the above lower limit, the rigidity and mechanical strength are improved, and when it is equal to or lower than the above upper limit, the low-temperature impact resistance is good.

[0061] As described above, the thermoplastic elastomer composition of the present invention has an essential requirement that the mass of component (B) / the mass of component (A) is 0.6 or more from the viewpoint of further improving low-temperature impact resistance without impairing high-temperature strength and releasability, but this mass ratio is preferably 0.7 or more, and more preferably 0.8 or more, from the viewpoint of further improving low-temperature impact resistance without impairing high-temperature strength and releasability. On the other hand, from the viewpoint of satisfying the preferable requirement of the content of component (A)>the content of component (B), the ratio of the mass of component (B) / the mass of component (A) is preferably less than 1.0, more preferably 0.99 or less, and even more preferably 0.98 or less.

[0062] <Other ingredients> In addition to the above-mentioned components (A) to (C), the thermoplastic elastomer composition of the present invention may contain optional components such as the following additives, inorganic fillers, organic fillers, and resins other than components (A) to (C) (hereinafter referred to as "other resins") according to various purposes, within the scope of not significantly impairing the effects of the present invention.

[0063] Examples of additives include various additives such as colorants, antioxidants, heat stabilizers, light stabilizers, ultraviolet absorbers, neutralizing agents, lubricants, antifogging agents, antiblocking agents, slip agents, flame retardants, dispersants, antistatic agents, conductivity imparting agents, metal deactivators, molecular weight regulators, antibacterial agents, fluorescent whitening agents, etc. These additives can be used by blending each additive in an amount of 0.01 to 2 parts by mass per 100 parts by mass of the total of components (A) to (C).

[0064] Examples of other resins that may be contained in the thermoplastic elastomer composition of the present invention include low-density polyethylene, polyester elastomer, urethane elastomer, polyester resin, polyamide resin, polyurethane resin, styrene resin, polycarbonate resin, polyvinyl chloride resin, and various other elastomers (excluding those corresponding to component (B)). The other resins listed above may be contained alone or in combination of two or more. When the thermoplastic elastomer composition of the present invention contains other resins, in order to more effectively obtain the effects of the present invention by containing components (A) to (C), the content of the other resins is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less, based on the total of components (A) to (C) and the other resins.

[0065] <Crosslinking agent> The thermoplastic elastomer composition of the present invention may contain the above-mentioned components and may be partially crosslinked. In this case, the crosslinking method is not particularly limited, but it is usually preferable to dynamically heat-treat (dynamically crosslink) the composition in the presence of a crosslinking agent from the viewpoint of improving rubber elasticity and extrusion moldability.

[0066] Here, dynamic heat treatment (dynamic heat treatment) means kneading in a molten or semi-molten state. Dynamic heat treatment is usually carried out by uniformly mixing the above-mentioned components and then melt-kneading them in the presence of a crosslinking agent and, if necessary, a crosslinking assistant.

[0067] As a crosslinking agent for partially crosslinking the thermoplastic elastomer composition of the present invention, it is preferable to use an organic peroxide, and examples of such a crosslinking agent include 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, 1,3-bis(t-butylperoxyisopropyl)benzene, 1,1-di(t-butylperoxy)3,5,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(peroxybenzoyl)hexyne-3, and dicumyl peroxide.

[0068] Examples of crosslinking aids used in partial crosslinking with these organic peroxides include compounds having a radically polymerizable carbon-carbon double bond, such as N,N'-m-phenylene bismaleimide, toluylene bismaleimide, p-quinone dioxime, nitrobenzene, diphenyl guanidine, trimethylolpropane, divinylbenzene, ethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, and allyl methacrylate, and compounds having a functional group that reacts with the linear carbon chain portion of component (A) and / or component (B).

[0069] The proportion of the crosslinking agent used is usually 0.01 to 3 parts by mass, and preferably 0.04 to 1 part by mass, per 100 parts by mass of the components (A) to (C).

[0070] <Method of producing thermoplastic elastomer composition> The thermoplastic elastomer composition of the present invention can be produced by kneading the above-mentioned components (A) to (C) and other components used as necessary in a conventional manner using a conventional extruder, Banbury mixer, roll, Brabender Plastograph, Kneader Brabender, etc. Among these production methods, it is preferable to use an extruder, particularly a twin-screw extruder.

[0071] When the thermoplastic elastomer composition of the present invention is produced by kneading it with an extruder or the like, it is melt-kneaded in a heated state usually at 155 to 240° C., preferably 180 to 220° C. At this time, the above-mentioned crosslinking agent or crosslinking aid can be blended and dynamically heat-treated to partially crosslink it.

[0072] <Physical Properties> The thermoplastic elastomer of the present invention contains the above-mentioned components (A) to (C) and is therefore excellent in high-temperature strength, low-temperature impact resistance, and mold releasability. The thermoplastic elastomer composition of the present invention preferably has the following physical properties.

[0073] (Izod impact strength) In the present invention, the Izod impact strength at -45°C, -50°C and -55°C according to JIS K7110 (1999) is used as an index of low-temperature impact resistance. The Izod impact strength of the molded product of the thermoplastic elastomer composition of the present invention is 50 kJ / m 2 It is preferable that the concentration is 70 kJ / m or more. 2 More preferably, it is 90 kJ / m or more. 2 On the other hand, the upper limit of the Izod impact strength of the thermoplastic elastomer composition of the present invention is not particularly limited, but is usually 150 kJ / m 2 The following is the result.

[0074] (MFR) In the present invention, the melt flow rate (MFR) at a temperature of 230°C and a measuring load of 21.18N according to JIS K7210 (1999) is used as an index of the injection moldability of the thermoplastic elastomer composition. In order to make the thermoplastic elastomer composition of the present invention excellent in injection moldability, the melt flow rate is preferably 1.0 to 10 g / 10 min. If the MFR of the thermoplastic elastomer composition is 1.0 g / 10 min or more, the flowability tends to be good, and if it is 10 g / 10 or less, it is preferable because burrs and the like during molding can be easily suppressed. From the viewpoint of flowability, the MFR of the thermoplastic elastomer composition is more preferably 2.0 g / 10 min or more, and even more preferably 2.5 g / 10 min or more. On the other hand, from the viewpoint of suppressing burrs and the like during injection molding, the MFR of the thermoplastic elastomer composition is more preferably 9.0 g / 10 min or less, even more preferably 8.0 g / 10 min or less, and particularly preferably 7.0 g / 10 min or less.

[0075] (Room temperature tensile elongation at break) From the viewpoint of material strength, the thermoplastic elastomer composition of the present invention preferably has a tensile elongation at break of 300% or more, more preferably 350% or more, at 23°C according to JIS K6251. When a composition having a tensile elongation at break of less than the lower limit is used, the elongation of the material is poor, and the unfoldability of the airbag storage cover tends to decrease. The upper limit of the tensile elongation at break of the thermoplastic elastomer composition of the present invention is not particularly limited, but is usually 1500% or less.

[0076] (High temperature tensile strength) From the viewpoint of material strength, the thermoplastic elastomer composition of the present invention preferably has a tensile breaking strength at 85°C according to JIS K6251 of 4 MPa or more, more preferably 4.5 MPa or more. If a composition having a tensile breaking strength at 85°C below the lower limit is used, the material strength is inferior and the unfoldability of the airbag storage cover tends to decrease. The upper limit of the tensile breaking strength of the thermoplastic elastomer composition of the present invention is not particularly limited, but is usually 6 MPa or less.

[0077] (Flexural modulus) The thermoplastic elastomer composition of the present invention preferably has a flexural modulus of 600 MPa or less, particularly 200 to 550 MPa, measured in accordance with JIS K7203. If the flexural modulus of the thermoplastic elastomer composition is greater than the upper limit, low-temperature impact resistance tends to decrease, whereas if it is less than the lower limit, rigidity tends to be insufficient.

[0078] <Molded article of thermoplastic elastomer composition> The thermoplastic elastomer composition of the present invention can be used as an airbag housing cover by forming a molded article using a normal injection molding method or, if necessary, various molding methods such as gas injection molding, injection compression molding, short shot foam molding, etc. In particular, it is preferable to form a molded article by injection molding the thermoplastic elastomer of the present invention, and the molding conditions for injection molding are as follows. The molding temperature when the thermoplastic elastomer composition is injection molded is usually 150 to 300° C., and preferably 180 to 280° C. The injection pressure is usually 5 to 100 MPa, and preferably 10 to 80 MPa. The mold temperature is usually 0 to 80° C., and preferably 20 to 60° C.

[0079] <Application> The thermoplastic elastomer composition of the present invention has excellent high-temperature strength, low-temperature impact resistance, and mold releasability, and is suitable for use as a molding material for airbag storage covers, particularly for airbag storage covers for airbag systems that detect impact or deformation in the event of a collision or other accident involving a high-speed moving object such as an automobile, and are activated by inflating and deploying to protect the occupant.

[0080] The thermoplastic elastomer composition of the present invention, having excellent high-temperature strength, low-temperature impact resistance, and mold releasability, can be suitably used for various applications other than airbag storage covers, such as instrument panels, center panels, center console boxes, door trims, pillars, assist grips, handles, and other automobile interior parts, mudguards, chromets, and other automobile exterior parts, home appliance parts, building materials, furniture, and the like. EXAMPLES

[0081] The present invention will be described in more detail below using examples, but the present invention is not limited to the following examples as long as it does not exceed the gist of the invention. The values ​​of various production conditions and evaluation results in the following examples are meant as preferred upper or lower limit values ​​in the embodiment of the present invention, and the preferred range may be a range defined by a combination of the above-mentioned upper or lower limit values ​​and the values ​​of the following examples or values ​​of the examples.

[0082] <Raw materials> [Component (A)] A-1: Novatec (registered trademark) PP BC03B manufactured by Japan Polypropylene Corporation Propylene Block Copolymer A product obtained by polymerizing propylene homopolymer in the first step, followed by polymerization of ethylene-propylene copolymer in the second step. MFR (JIS K7210 (1999)): 30g / 10 minutes (measurement conditions: 230℃, load 21.18N (2.16kgf)) Propylene homopolymer block content: 84% by mass Ethylene-propylene copolymer block content: 16% by mass Ethylene unit content in ethylene-propylene copolymer block: 55% by mass

[0083] [Component (B)] B-1: Engage (registered trademark) XLT8677 manufactured by Dow Chemical Company Block copolymers containing ethylene blocks and ethylene-1-octene copolymer blocks Crystal melting peak temperature: 119℃ Heat of crystal fusion: 37J / g MFR (ASTM D1238): 0.5g / 10min (measurement conditions: 190℃, load 21.18N (2.16kgf) (catalog value) Glass transition temperature (DSC method): -67℃ Density: (ISO 1183-A method): 0.872g / cm 3 (Measurement temperature: 23℃)

[0084] [Component (C)] C-1: Novatec (registered trademark) HD ​​HB330 manufactured by Japan Polyethylene Corporation High density polyethylene resin Density (JIS K6760): 0.953g / cm 3 MFR (ASTM D1238): 0.35g / 10 minutes (measurement conditions: 190℃, load 21.2N (2.16kgf))

[0085] [Component (D)] D-1: Engage(R) 8180 manufactured by Dow Chemical Company Ethylene-1-octene random copolymer Crystal melting peak: No peak at 110-125℃ Heat of crystal fusion: 0 MFR (ASTM D1238): 0.5g / 10min (measurement conditions: 190℃, load 21.18N (2.16kgf)) (catalog value) Density: 0.863g / cm 3

[0086] [Component (E)] E-1: Toughmer (registered trademark) A1050S manufactured by Mitsui Chemicals, Inc. Ethylene-1-butene random copolymer Density: 0.86g / cm 3 MFR: 1.2g / 10min (measurement conditions: 190℃, load 21.2N) Mooney viscosity ML1+4(100℃):40

[0087] [Component (F)] F-1: Toughmer (registered trademark) XM7090 manufactured by Mitsui Chemicals Propylene-1-butene random copolymer MFR(ASTM D1238):7g / 10min

[0088] [Component (G)] G-1: Sabic LLDPE M200024 Low Density Polyethylene Resin MFR (ASTM D1238): 20g / 10min (measurement conditions: 190℃, load 21.18N (2.16kgf)) (catalog value) Density: 0.924g / cm 3 (catalog value)

[0089] [Component (H)] H-1: Kayahexa AD40C manufactured by Kayaku Akzo Co., Ltd. A mixture of 40% by mass of 2,5-dimethyl-2,5-di(t-butylperoxy)hexane and 60% by mass of calcium carbonate

[0090] <Evaluation method> 1) Injection moldability: Melt flow rate Measurements were performed according to JIS K7210 (1999) at a temperature of 230°C and a load of 21.18N.

[0091] In the evaluations of 2) to 6) below, the thermoplastic elastomer composition pellets obtained in each example were used to injection mold test sheets for each test using an in-line screw type injection molding machine (Toshiba Machine Co., Ltd., "IS130") at an injection pressure of 50 MPa, a cylinder setting temperature of 220°C, and a mold temperature of 40°C.

[0092] 2) Low temperature impact resistance: Izod impact strength Using the above injection molding, notched test pieces for measuring Izod impact strength, 4 mm thick x 12.7 mm wide x 64 mm long, were molded and measured at temperatures of -45°C, -50°C, and -55°C in accordance with JIS K7110 (1999). In addition, non-destructive tests were rated as "NB", those that were on the verge of destruction with only a layer of skin remaining were rated as "H", and those that were destroyed were rated as "C". The higher the Izod impact strength value, and the more non-destructive "NB" samples were, the more excellent the low-temperature impact resistance was evaluated.

[0093] 3) Flexural modulus (unit: MPa) The measurements were performed in accordance with JIS K7203 under conditions of a span of 64 mm and a bending speed of 1 mm / min.

[0094] 4) Tensile elongation at break (23°C): Tensile breaking test (JIS-3 dumbbell, tensile speed 500mm / min) (unit:%) A test piece for a tensile test (a sheet having a thickness of 2 mm, a width of 120 mm, and a length of 80 mm) was punched out in accordance with JIS K6251 (JIS No. 3 dumbbell). The tensile elongation at break of the punched test piece was measured in an atmosphere of 23° C. in accordance with JIS K6251. The larger the value of the tensile elongation at break, the better the evaluation.

[0095] 5) Tensile breaking strength (85℃): Tensile breaking test (JIS-3 dumbbell, tensile speed 500mm / min (unit: MPa) A test piece for a tensile test (a sheet having a thickness of 2 mm, a width of 120 mm, and a length of 80 mm) was punched out in accordance with JIS K6251 (JIS No. 3 dumbbell). The tensile breaking strength of the punched test piece was measured in an atmosphere at 85°C in accordance with JIS K6251. The higher the value of the tensile breaking strength, the better the high-temperature strength was evaluated to be.

[0096] 6) Glossiness An injection-molded sheet with a thickness of 2 mm, width of 120 mm, and length of 80 mm was measured at an incidence angle of 60° in accordance with JIS Z8741. The smaller the gloss value, the better the release property was evaluated to be.

[0097] <Examples / Comparative Examples> [Example 1] As shown in Table 1, 48 parts by mass of (A-1), 47 parts by mass of (B-1), 5 parts by mass of (C-1), and 100 parts by mass of (A-1), (B-1), and (C-1) were blended for 1 minute in a Henschel mixer with 0.1 parts by mass of an antioxidant (manufactured by BASF Japan Ltd., product name Irganox (registered trademark) 1010FF), 0.1 parts by mass of HALS (manufactured by BASF Japan Ltd., Tinuvin XT855FF), 0.2 parts by mass of silicone oil (manufactured by Shin-Etsu Chemical Co., Ltd., KF96-100CS), and 1.5 parts by mass of a black pigment (carbon concentration of 40% by mass). The blend was fed into a co-rotating twin-screw extruder (Toshiba Machine Co., Ltd. "TEM-26SS", L / D=48.5, number of cylinder blocks: 12) at a rate of 25 kg / h, and melt-kneaded by heating in the range of 160 to 210°C to produce pellets of a thermoplastic elastomer composition. The obtained pellets of the thermoplastic elastomer composition were evaluated in the above items 1) to 6). The evaluation results are shown in Table 1.

[0098] [Examples 2 to 4 and Comparative Examples 1 to 5] Pellets of a thermoplastic elastomer composition were obtained in the same manner as in Example 1, except that the blending ratio was as shown in Table 1 (however, 0.1 parts by mass of antioxidant, 0.1 parts by mass of HALS, and 1.5 parts by mass of black pigment were blended with respect to a total of 100 parts by mass of components (A) to (G). The blending amounts of these are omitted in Table 1). Furthermore, evaluations 1) to 6) were performed in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0099] [Table 1]

[0100] [Evaluation Results] In Examples 1 to 4, due to the incorporation of components (A) to (C), in addition to excellent low-temperature impact resistance, high-temperature strength and releasability were also good. On the other hand, in Comparative Example 1, which did not contain component (C) but contained only components (A) and (B), the mold releasability was poor. Comparative Example 2 did not contain component (B) but contained components (A), (C), (E), (F) and (H), but the low-temperature impact resistance, high-temperature strength and releasability were poor. In Comparative Example 3, the amount of component (A) used was large and the amount of component (B) used was small, but the low-temperature impact resistance was poor. Comparative Example 4 was a blend of components (A), (B) and (C), but the ratio of component (B) / component (A) was small, and the low-temperature impact resistance and releasability were poor. Comparative Example 5 did not contain component (B) but contained components (A), (C), (D), (E) and (G), and the low-temperature impact resistance and high-temperature strength were poor. [Industrial Applicability]

[0101] The thermoplastic elastomer composition of the present invention has excellent high-temperature strength, low-temperature impact resistance, and mold releasability, and is suitable, for example, as a molding material for an airbag storage cover of an airbag system that activates upon sensing the impact or deformation of a collision accident or the like of a high-speed moving body such as an automobile, and protects occupants by inflating and deploying.

Claims

1. A thermoplastic elastomer composition comprising at least the following components (A) to (C), wherein the composition comprises 25 to 60 mass% of component (A), 20 to 55 mass% of component (B), and 3 to 25 mass% of component (C) in a total of 100 mass% of components (A) to (C), and wherein the ratio of mass of component (B) to mass of component (A) is 0.6 or more. Component (A): A propylene-based block copolymer containing 15% by mass or less of ethylene units, α-olefin units other than propylene, and monomer units other than ethylene and α-olefins. Component (B): an olefin-based block copolymer containing a polymer block made of ethylene and an ethylene / α-olefin copolymer block. Component (C): High density polyethylene

2. The thermoplastic elastomer composition according to claim 1, wherein the contents of components (A) to (C) in the thermoplastic elastomer composition are such that the content of component (A) > the content of component (B) > the content of component (C).

3. The thermoplastic elastomer composition according to claim 1 or 2, wherein the component (B) has a crystalline melting peak at 110 to 125° C. and a crystalline melting heat of 20 to 60 J / g.

4. 4. The thermoplastic elastomer composition according to claim 1, wherein the α-olefin in the ethylene / α-olefin copolymer block of the component (B) has 4 to 8 carbon atoms.

5. The thermoplastic elastomer composition according to any one of claims 1 to 4, wherein the component (B) is an olefin-based block copolymer containing a polymer block made of ethylene and an ethylene-1-octene copolymer block.

6. The thermoplastic elastomer composition according to any one of claims 1 to 5, wherein the component (A) is a propylene-based block copolymer obtained by polymerizing a propylene homopolymer in a first step and subsequently polymerizing a propylene-ethylene copolymer in a second step.

7. The thermoplastic elastomer composition according to any one of claims 1 to 6, wherein the melt flow rate of the component (A) (measurement temperature: 230°C, measurement load: 21.18N) is 10 to 150 g / 10 min.

8. A molded article obtained by injection molding the thermoplastic elastomer composition according to any one of claims 1 to 7.

9. An airbag storage cover comprising the thermoplastic elastomer composition according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Polypropylene composition and molded article of the same

    JP2013203937A

  • Propylene resin composition

    JP2014001343A

  • Air bag housing cover

    JP2014077128A

  • Thermoplastic elastomer composition

    JP2018035297A

  • Thermoplastic elastomer composition, molded article and air bag housing cover

    JP2019038925A